Recurrence Is a Noticeable Cause of Rifampicin-Resistant Mycobacterium tuberculosis in the Elderly Population in Jiangxi, China - Chen, Qiang; Peng, Linfeng; Xiong, Guangchu; Peng, Yiping; Luo, Dong; Zou, Lijin; Chen, Kaisen (Frontiers in Public Health, 2019)
Rifampicin-resistant tuberculosis (RR-TB) is widespread in elder people in Jiangxi Province, China, but the cause is unknown. This study would investigate the incidence of RR-TB and risk factors in elder people within a hospital setting in China. Here, we performed retrospective cohort study, including a comparative study to analyse RR-TB with rifampicin-susceptible TB (RS-TB) and 15-loci MIRU-VNTR method to determine relapse or reinfection. The results showed 23 recurrent cases existed in 151 RR-TB elderly tuberculosis patients, correspondingly, 24 in 466 RS-TB cases during this period. At the same time, elderly TB recurrence had significant difference between RR-TB and RS-TB (OR=0.35, 95%CI: 0.14-0.88; 2=5.28, P = 0.03). Comparing the risk factors of RR-TB and RS-TB in elderly patients, education level, age and pulmonary cavity were inextricably linked to elderly RR-TB. Furthermore, pulmonary cavity, HIV infection and alcohol consumption were associated with elderly RR-TB recurrence. These findings proved recurrence was an important source of elderly RR-TB, and elderly RR-TB prevention needs to focus on standard treatment.